Humoral primary immunodeficiency diseases: clinical overview and chest high-resolution computed tomography (HRCT) features in the adult population. Issue 7 (July 2017) - Cereser, L.; Girometti, R.; d'Angelo, P.; De Carli, M.; De Pellegrin, A.; Zuiani, C.
Abstract : Humoral primary immunodeficiency diseases (hPIDs) are a heterogeneous group of hereditary disorders resulting in abnormal susceptibility to infections of the sinopulmonary tract. Some of these conditions (e.g., common variable immunodeficiency disorders [CVID]) imply a number of non-infectious thoracic complications such as non-infectious airway disorders, diffuse lung parenchymal diseases, and neoplasms. Chest high-resolution computed tomography (HRCT) is a key imaging tool to characterise and quantify the extent of underlying thoracic involvement, as well as to direct and monitor treatment. The aims of this review are to provide a brief clinical overview of hPIDs and describe the related chest HRCT imaging features in the adult population, with a special focus on CVID and its complications.